1957
DOI: 10.1002/cber.19570900712
|View full text |Cite
|
Sign up to set email alerts
|

Eine Neue Darstellungsweise von Aminen aus α‐Aminocarbonsäuren

Abstract: Eine Methode zur Darstellung von Aminen aus a-Aminocarbonsiluren durch Decarboxylierung bei Gegenwart aromatischer Aldehyde wird beschrieben und der Mechanismus dieser Reaktion elektronentheoretisch gedeutet. Die Reaktionsgemische werden durch Hochspannungspherographie im mikropraparativen und analytischen MaBstab aufgetrennt und u. a. mit Hilfe kolorimetrischer Methoden bestimmt.Die bekannten naturlichen a-Aminocarbonsauren lassen sich teilweise, wenn auch unter erheblichen Verlusten. durch einfaches Erhitzen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…However, when no copper catalyst is used, only a trace amount of the coupling product 4o was observed with GC-MS analysis (Scheme ). These results confirmed that aldehyde is essential to induce decarboxylation , and CuI catalyst is important in the C−C bond formation step.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…However, when no copper catalyst is used, only a trace amount of the coupling product 4o was observed with GC-MS analysis (Scheme ). These results confirmed that aldehyde is essential to induce decarboxylation , and CuI catalyst is important in the C−C bond formation step.…”
Section: Resultssupporting
confidence: 69%
“…Meanwhile, the use of benzaldehyde bearing an electron-withdrawing group at different positions gave the corresponding products 4h , 4i , and 4j , respectively (entries 8−10). However, benzaldehyde bearing an electron-donating group gave a lower yield (entry 11) . When 4-methoxybenzaldehyde 1f was used, two types of C−C bond formation products 4 l and 5a were obtained (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…These aldehydes and ketones interact with the amino acid to generate a Schiff base adduct (Scheme ), thereby mimicking the mode of operation of pyridoxal 5′‐phosphate and the pyruvoyl cofactor in amino acid decarboxylases. Whereas the enzymatic reactions typically proceed in aqueous media under very mild conditions, chemocatalytic decarboxylation is generally performed at higher temperatures (e.g., 120–270 °C), hence in high‐boiling and often toxic organic solvents such as nitrobenzene, N , N ‐dimethylformamide, hexamethyl phosphoramide or cyclohexanol . Water has an adverse effect on the Schiff‐base equilibrium and should therefore be avoided in the process medium.…”
Section: Amino Acids As Direct Precursors To Value‐added Chemicalsmentioning
confidence: 99%
“…Transamination is more pronounced when using aromatic aldehydes and ketones with an electron‐withdrawing substituent at the ortho or para position of the ring, because the negative charge of the carbanion will be located mainly on the γ‐carbon. However, aromatic carbonyl compounds with electron‐donating substituents keep the negative charge located on the α‐carbon center, and reduce the tendency towards transamination . De Vos and co‐workers evaluated various types of carbonyl compounds in the decarboxylation of phenylalanine and elucidated that the reaction rate is strongly determined by the molecular structure of both the catalyst and the substrate.…”
Section: Amino Acids As Direct Precursors To Value‐added Chemicalsmentioning
confidence: 99%
“…Conversion AA into primary amines is mainly performed via enzymatic , or chemocatalytic decarboxylation. This latter step is often still performed in toxic organic solvents (e.g., nitrobenzene, chloroethane), at high temperatures (120–270 °C), with large excess of decarboxylating agent (aldehyde and ketone to form Schiff-base adduct) or with noble-metal catalysts (e.g., Pd-based materials , ).…”
Section: Demonstrated Electrochemical Routes For Conversion Of Interm...mentioning
confidence: 99%